(3GdJeKGd hGdeMGVQIs - (3GdKYGdHj GdfjSGHhQj, CHh efUhQ, YHO Gdedc Hf eMeO Hf ESeGYjd, J (B429 (3g`s ((3eMeO Hf eMeO Hf GdegJGQ GdeDPfs)
(3ChdgG (B:s
(3GdaUd GdChd ef GdcJGH aj GdeONd hGdCfehPL eeG jLQj eLQi GdCeKGd ef PcQ Gddg JYGdi aj afhf GdCZQGV hGdebGUO ef Pdc dWGFa GdJMejO GdMeO ddg TYGQ Cgd GdLfIs
(3BNQgG (B:s
(3YeQQ Hf YHO GdYRjR QVj Gddg Yfg CMH GdCTjGA Edi Gddg CQHYI GdbUO YfO GdMOI hGdYah YfO GdebOQI hGdMde YfO GdZVH hGdQab HYHGO Gddg aj cd MGd (B, (3GdeCehf GdfGS CQHY WHbGJ Je GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4/163s
(3cTa GdXfhf (B1/ 483s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs